Anadolu Uygarlıkları'nda seramik formlarda kulp-emzik ilişkisi (M.Ö. 8000-M.S. 17. yy.) - Yılmaz, Zekeriya (My University, 2001)
İnsan belirgin anlamı ile yaratıcı ve üretici olma durumuna M. Ö. 10. 000 sıralarında, göçebelikten yerleşik düzene geçtikten ve onun ardından da M. Ö. 3000 dolaylarında yazıyı icat edip kullanmayı başardıktan sonra ulaşmıştır...» (5) Yazının icadıyla başlayan devirlere Tarihsel Çağlar, yazının bilinmediği devirlere de Tarih Öncesi Çağlar adı verilmektedir. Çağların incelenmesi suretiyle; insanoğlunun kat ettiği gelişim süreci, yazının icadı ile başlayan; yerleşik düzen, ticaret alışkanlığı, alfabenin kullanımı ile insanlığın bilgi birikimini aktarması, bilim ve kültür alanında kat ettiği yol, yerleşik düzene geçiş sonrası yaşamı ve etkileyen faktörleri anlama kolaylığı sağlamaktadır. Araştırma çalışması ile; Bilgi, bilim ve kültür birikimini aktarması süreci içerisinde teori olarak verilen Tarihi Çağlar, Anadolu Uygarlıkları çerçevesi içerisinde işlenmiş, bu süreç içerisinde kat ettiği yollar, çağın gerekliliği çerçevesinde; seramik, taş, metal formlar olarak kronolojik sıra ile ele alınmış, biçimsel karşılaştırma yapma imkanı yaratılmıştır. (5) Anadolu Kültür Tarihi. Ekrem Akurgal. Tûbltak Popüler Bilim Kitapları, 5. Basım. Syf.2 IV

The aim of this study, by analyzing Anatolian civilizations one by one is to show local art tradition that has been lasting for centuries, perceive cultural components of Anatolia, creativity and continual qualify of peninsula despite of external effects and relations. Finally, it is to have an analyze by comparing these processes. Anatolia beside, being a bridge that combines east and west to each other, is a land in which specific civilizations providing improvements to human life are created. It is seen that different types of specific, developed civilizations and art centers had been established in Anatolia which had been affected by different types of nations in past. Different types of regions taking part in Anatolia have helped those civilizations develop and have local features. The works included in this study is considered according to chronology and places of excavation. Documents gathered from museums located in Ankara and İstanbul and other museums are considered and other resources related to this study are used to provide an analyze of those works belonging to Anatolian Civilizations since B.C. 50.000 and of beliefs, social and cultural lives of people creating those works. Topics theoretically considered as Prehistoric Periods and The Historical Periods are supported by formal comparisons done chronologically. V
Keywords: Arkeoloji; Güzel ve dekoratif sanatlar; Prehistorya; Seramik sanatları; Seramikler; Uygarlık, Anadolu